Two-component developer and image formation device

The two-component developer, with optimized carrier and toner particle compositions and coverage, addresses the issues of image density stability and fog suppression in electrophotography, resulting in high-quality image formation.

JP2025052657APending Publication Date: 2025-04-07KYOCERA DOCUMENT SOLUTIONS INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023161474
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-25
Publication Date
2025-04-07

AI Technical Summary

Technical Problem

Existing two-component developers for electrophotography fail to achieve adequate image density stability and suppress fog generation effectively.

Method used

A two-component developer comprising carrier particles with a carrier core, a coating layer containing silicone resin, barium titanate particles, and carbon black, and toner particles with toner base particles and external additives including spacer particles, where the coverage and desorption rates of these particles are optimized to satisfy specific formulas.

Benefits of technology

The developer achieves excellent image density stability and effectively suppresses fog generation, ensuring high-quality image formation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025052657000001_ABST
    Figure 2025052657000001_ABST
Patent Text Reader

Abstract

To provide a two-component developer which is excellent in image density stability and can suppress occurrence of fogging.SOLUTION: A two-component developer contains a carrier containing carrier particles, and a toner containing toner particles. The carrier particles have carrier base particles, and strontium titanate particles attached to the surface of the carrier base particles. The carrier base particles have a carrier core, and a coat layer coating the carrier core. The coat layer contains a coat resin, barium titanate particles and a carbon black. The coat resin contains a silicone resin. The toner particles have toner base particles, and an external additive attached to the surface of the toner base particles. The external additive contains silica particles, and spacer particles. A number average primary particle diameter of the spacer particles is 35 nm or more and 200 nm or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a two-component developer and an image forming apparatus. [Background technology]

[0002] In the electrophotographic method, for example, a two-component developer including a carrier containing carrier particles and a toner containing toner particles is used. The two-component developer is required to have excellent image density stability and to be able to suppress the occurrence of fogging.

[0003] In response to such demands, for example, it has been proposed to use a carrier for electrophotographic developer in which a carrier core material is coated with a resin layer, and in which at least one type of additive used in the toner has been added and mixed in advance in a process prior to mixing with the toner (Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2005-91878 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, even the two-component developer using the carrier described in Patent Document 1 cannot fully satisfy the requirements for image density stability and suppression of the occurrence of fogging.

[0006] The present invention has been made in consideration of the above-mentioned problems, and an object of the present invention is to provide a two-component developer that has excellent image density stability and can suppress the occurrence of fogging, and an image forming apparatus that uses this two-component developer. [Means for solving the problem]

[0007] The two-component developer of the present invention includes a carrier including carrier particles and a toner including toner particles. The carrier particles include carrier base particles and strontium titanate particles adhering to the surfaces of the carrier base particles. The carrier base particles include a carrier core and a coating layer that covers the carrier core. The coating layer contains a coating resin, barium titanate particles, and carbon black. The coating resin contains a silicone resin. The toner particles include toner base particles and an external additive that adheres to the surfaces of the toner base particles. The external additive includes silica particles and spacer particles. The number-average primary particle diameter of the spacer particles is 35 nm or more and 200 nm or less. The coverage A of the spacer particles on the toner particles and the coverage B of the strontium titanate particles on the carrier particles satisfy the following formula (1). The detachment rate M of the spacer particles calculated by the following formula (M) and the detachment rate N of the strontium titanate particles calculated by the following formula (N) satisfy the following formula (2). A>B···(1) N>M···(2) M = 100 × (M1 - M2) / M1 (M) N = 100 × (N1 - N2) / N1 (N)

[0008] In the formulas (M) and (N), M1 represents the content of the spacer particles in the toner particles. M2 represents the content of the spacer particles in the toner particles after a printing durability test. N1 represents the content of the strontium titanate particles in the carrier particles. N2 represents the content of the strontium titanate particles in the carrier particles after the printing durability test. The printing durability test is a test in which a pattern image with a printing rate of 1% is intermittently printed on 1,000 sheets of A4 size printing paper, one by one, using the two-component developer, in an environment of a temperature of 23.5° C. and a humidity of 5% RH.

[0009] The image forming apparatus of the present invention includes the above-mentioned two-component developer, a photoconductor, a charging device for charging the surface of the photoconductor, and a developing device for supplying the toner to the surface of the photoconductor and developing it into a toner image. The printing durability test is performed using the image forming apparatus. Effect of the Invention

[0010] The two-component developer and image forming apparatus of the present invention are excellent in image density stability and can suppress the occurrence of fogging. [Brief description of the drawings]

[0011] [Figure 1] 3A and 3B are diagrams illustrating an example of carrier particles and toner particles included in a two-component developer according to a first embodiment. [Diagram 2] FIG. 13 illustrates an example of an image forming apparatus according to a second embodiment. [Diagram 3] 3 is a diagram showing a developing device and its surroundings provided in the image forming apparatus in FIG. 2; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] A preferred embodiment of the present invention will be described below. The carrier is an aggregate (e.g., powder) of carrier particles. The toner is an aggregate (e.g., powder) of toner particles. The external additive (silica particles and spacer particles) is an aggregate (e.g., powder) of external additive particles. Unless otherwise specified, the evaluation results (values ​​indicating shape, physical properties, etc.) of the powder (more specifically, the powder of toner particles, the powder of external additive particles, the magnetic powder, the powder of carrier particles, etc.) are the number average of values ​​measured for each of a considerable number of particles selected from the powder.

[0013] Volume median diameter of powder (D 50 ) is a value measured using a laser diffraction / scattering particle size distribution analyzer (e.g., HORIBA, Ltd.'s "LA-920V2" or Beckman Coulter, Inc.'s "Coulter Counter Multisizer 3" unless otherwise specified.

[0014] Unless otherwise specified, the number average primary particle diameter of a powder is the number average value of the circle equivalent diameters of primary particles (Heywood diameter: diameter of a circle having the same area as the projected area of ​​a primary particle) measured using a scanning electron microscope. The number average primary particle diameter of a powder is, for example, the number average value of the circle equivalent diameters of 100 primary particles. The number average primary particle diameter of particles refers to the number average primary particle diameter of particles in the powder unless otherwise specified.

[0015] Unless otherwise specified, the chargeability refers to the chargeability in triboelectric charging. For example, a standard carrier (standard carrier for negatively charged toner: N-01, standard carrier for positively charged toner: P-01) provided by the Imaging Society of Japan is mixed with the measurement target (e.g., toner) and stirred to triboelectrically charge the measurement target. The charge amount of the measurement target is measured before and after triboelectric charging, for example, with a small suction-type charge amount measuring device (Trek's "MODEL 212HS"), and the greater the change in charge amount before and after triboelectric charging, the stronger the chargeability of the measurement target.

[0016] Unless otherwise specified, the "major component" of a material means the component that is contained in the largest amount in the material on a mass basis.

[0017] The glass transition point (Tg) and melting point (Mp) are values ​​measured according to JIS (Japanese Industrial Standards) K7121-2012 using a differential scanning calorimeter (Seiko Instruments Inc.'s "DSC-6220") unless otherwise specified. In the endothermic curve of a sample measured with a differential scanning calorimeter (vertical axis: heat flow (DSC signal), horizontal axis: temperature), the temperature of the inflection point due to glass transition is the glass transition point (Tg). In detail, the temperature of the inflection point due to glass transition is the temperature of the intersection between the extrapolated line of the baseline and the extrapolated line of the falling line. The temperature of the maximum endothermic peak in the endothermic curve is the melting point (Mp). The softening point (Tm) is a value measured using a high-temperature flow tester (Shimadzu Corporation's "CFT-500D") unless otherwise specified. In the S-shaped curve (horizontal axis: temperature, vertical axis: stroke) of a sample measured with a high-speed flow tester, the temperature at which "(baseline stroke value + maximum stroke value) / 2" is the softening point (Tm).

[0018] Hereinafter, the compound and its derivatives may be collectively referred to by adding "based" after the compound name. When the polymer name is expressed by adding "based" after the compound name, it means that the repeating unit of the polymer is derived from the compound or its derivative. Acrylic and methacrylic may be collectively referred to as "(meth)acrylic". Each component described below may be used alone or in combination of two or more types, unless otherwise specified.

[0019] <First embodiment: Two-component developer> The first embodiment of the present invention relates to a two-component developer (hereinafter, sometimes simply referred to as a developer). The developer of this embodiment includes a carrier including carrier particles and a toner including toner particles. The carrier particles include carrier base particles and strontium titanate particles attached to the surfaces of the carrier base particles. The carrier base particles include a carrier core and a coating layer that coats the carrier core. The coating layer contains a coating resin, barium titanate particles, and carbon black. The coating resin contains a silicone resin. The toner particles include toner base particles and an external additive that coats the surfaces of the toner base particles. The external additive includes silica particles (hereinafter, sometimes referred to as base silica particles) and spacer particles. The number-average primary particle diameter of the spacer particles is 35 nm or more and 200 nm or less. The coverage A of the spacer particles on the toner particles and the coverage B of the strontium titanate particles on the carrier particles satisfy the following formula (1). The detachment rate M of the spacer particles calculated by the following formula (M) and the detachment rate N of the strontium titanate particles calculated by the following formula (N) satisfy the following formula (2). A>B···(1) N>M···(2) M = 100 × (M1 - M2) / M1 (M) N = 100 × (N1 - N2) / N1 (N)

[0020] In formulas (M) and (N), M1 represents the content of spacer particles in the toner particles. M2 represents the content of spacer particles in the toner particles after the printing durability test. N1 represents the content of strontium titanate particles in the carrier particles. N2 represents the content of strontium titanate particles in the carrier particles after the printing durability test. The printing durability test is a test in which a pattern image with a print rate of 1% is intermittently printed on 1,000 sheets of A4 size printing paper using a developer in an environment of a temperature of 23.5°C and a humidity of 5% RH, one sheet at a time.

[0021] In the developer of the present embodiment, for example, the carrier and the toner are stirred in the developing device, so that the toner is charged. The developer of the present embodiment is suitable for an image forming apparatus of a so-called trickle development system, which will be described later in the second embodiment. In the image forming apparatus of the trickle development system, after starting development of an electrostatic latent image with an initial developer in the developing device, the developer in the developing device is discharged and a replenishment developer is replenished into the developing device, and the electrostatic latent image is developed with the developer in the developing device. During image formation, the carrier is replenished together with the toner into the developing device, and the carrier in the developing device is discharged in an amount that is excessive due to the replenishment, thereby suppressing deterioration of the carrier in the developing device. In addition, by suppressing deterioration of the carrier, the number of times the carrier in the developing device is replaced can be reduced. The developer of the present embodiment may be used as a developer (hereinafter, may be described as a general developer) for an image forming apparatus that does not use the trickle development system.

[0022] In general developers, the ratio of the toner mass to the carrier mass (100 x toner mass / carrier mass) is preferably 1% to 20%, more preferably 5% to 15%. In refill developers, the ratio of the carrier mass to the toner mass (100 x carrier mass / toner mass) is preferably 2% to 30%, more preferably 5% to 20%.

[0023] The developer of the present embodiment has the above-mentioned configuration, and is excellent in image density stability and can suppress the occurrence of fogging. The reason is explained below. The carrier of the developer of the present embodiment contains barium titanate particles in the coating layer of the carrier particles. Barium titanate particles are ferroelectric and have a high relative dielectric constant. Therefore, the carrier particles containing barium titanate particles in the coating layer have high charge retention ability. The carrier particles with high charge retention ability can continue to impart a sufficient amount of charge to the toner particles by contact with the toner particles. As a result, the developer of the present embodiment can stably form an image having a desired image density (excellent image density stability). In addition, the developer of the present embodiment can reduce the number of toner particles with insufficient charge and reversely charged toner particles, and suppress the occurrence of fogging, because the carrier particles can impart a sufficient amount of charge to the toner particles.

[0024] Furthermore, the coating layer of the carrier particles contains carbon black, which is a conductive material, and therefore has a certain degree of conductivity. As a result, in the developer of this embodiment, charge moves smoothly from the carrier particles to the toner particles. Furthermore, the carrier particles contain strontium titanate particles as an external carrier additive. The strontium titanate particles suppress excessive charging of the carrier particles (charge-up). As a result, the developer of this embodiment can more effectively suppress the occurrence of fogging while more effectively exhibiting excellent image density stability.

[0025] On the other hand, in a known developer containing carrier particles having strontium titanate particles, when the carrier particles come into contact with the toner particles, the strontium titanate particles come into contact with the base silica particles. As a result, in the known developer, phenomenon α occurs in which the strontium titanate particles bury the base silica particles in the toner mother particles, and phenomenon β occurs in which the strontium titanate particles peel off the surface treatment of the base silica particles. In contrast, in the developer of this embodiment, the toner particles have spacer particles. The spacer particles suppress the contact between the strontium titanate particles and the base silica particles. In particular, in the developer of this embodiment, the coverage A of the spacer particles is greater than the coverage B of the strontium titanate particles, so that the spacer particles function effectively. As a result, in the developer of this embodiment, the occurrence of the above-mentioned phenomenon α and phenomenon β caused by the strontium titanate particles can be suppressed.

[0026] In addition, with the developer of this embodiment, as image printing continues, the spacer particles are inevitably detached from the toner base particles, and the strontium titanate particles are inevitably detached from the carrier base particles. However, with the developer of this embodiment, the detachment rate M of the spacer particles is smaller than the detachment rate N of the strontium titanate particles. In other words, with the developer of this embodiment, the strontium titanate particles are detached from the carrier particles at a faster pace than the spacer particles are detached from the toner base particles. Therefore, the developer of this embodiment can continue to suppress the occurrence of the above-mentioned phenomenon α and phenomenon β caused by the strontium titanate particles.

[0027] Furthermore, in known developers containing toner particles having spacer particles, the spacer particles and the toner base particles are charged to the same polarity and electrostatically repel each other, so that the spacer particles tend to be easily detached from the toner base particles. In contrast, in the developer of the present embodiment, the carrier particles can remove the charge from the spacer particles due to the action of the strontium titanate particles contained as a carrier external additive and the barium titanate particles contained in the coating layer. That is, the carrier particles can reduce the charge amount of the spacer particles. In addition, the coating layer on the surface of the carrier particles contains a silicone resin, which is a resin with low adhesion. This allows the developer of the present embodiment to suppress the attachment of the spacer particles to the surface of the carrier particles. As a result, the developer of the present embodiment can suppress the detachment of the spacer particles from the toner base particles and reduce the above-mentioned detachment rate M of the spacer particles.

[0028] The carrier includes carrier particles. The toner includes toner particles. An example of the carrier particles and toner particles contained in the developer of this embodiment will be shown below with reference to FIG. 1. FIG. 1 shows carrier particles 1, which are an example of the carrier particles contained in the developer of this embodiment, and toner particles 4, which are an example of the toner particles contained in the developer of this embodiment. The carrier particles 1 include carrier base particles 2 and strontium titanate particles 3. The strontium titanate particles 3 are attached (provided) on the surface of the carrier base particles 2. The carrier base particles 2 include a carrier core 2a and a coating layer 2b. The coating layer 2b covers the entire surface of the carrier core 2a.

[0029] The toner particles 4 include toner base particles 5 and external additives 6. The toner base particles 5 are non-capsulated toner base particles. The external additives 6 are attached (provided) on the surfaces of the toner base particles 5. The external additives 6 include spacer particles 6a and base silica particles 6b. The external additives 6 may further include other external additives as necessary.

[0030] An example of the carrier particles and toner particles contained in the developer of the present embodiment has been described above with reference to Fig. 1. However, in the developer of the present embodiment, the structures of the carrier particles and toner particles are not limited to those shown in Fig. 1. For example, the toner base particles may be capsule toner base particles including a toner core and a shell layer that covers the toner core. The coat layer of the carrier particles may cover at least a part of the carrier core. That is, a part of the carrier core may be exposed.

[0031] In the developer of this embodiment, the coverage A of the spacer particles on the toner particles and the coverage B of the strontium titanate particles on the carrier particles satisfy the following formula (1). The coverage A of the spacer particles on the toner particles and the coverage B of the strontium titanate particles on the carrier particles preferably satisfy the following formula (1a), and more preferably satisfy the following formula (1b). A>B···(1) 30.0Area%>AB>5.0Area%...(1a) 15.0 area%>AB>8.0 area%...(1b)

[0032] The coverage A of the spacer particles in the toner particles is preferably 10.0 area% or more and 45.0 area% or less, more preferably 14.5 area% or more and 35.0 area% or less, and even more preferably 20.0 area% or more and 30.0 area% or less. By setting the coverage A to 10.0 area% or more, the developer of this embodiment is more likely to satisfy the above formula (1). By setting the coverage A to 45.0 area% or less, the charge amount of the toner can be optimized.

[0033] The coverage B of the strontium titanate particles on the carrier particles is preferably 5.0 area% or more and 20.0 area% or less, and more preferably 12.0 area% or more and 16.0 area% or less. By setting the coverage B to 5.0 area% or more, the developer of this embodiment can exhibit more excellent image density stability and can more appropriately suppress the occurrence of fogging. By setting the coverage B to 20.0 area% or less, the developer of this embodiment can easily satisfy the above formula (1).

[0034] In the developer of this embodiment, the detachment rate M of the spacer particles and the detachment rate N of the strontium titanate particles satisfy the following formula (2). The detachment rate M of the spacer particles and the detachment rate N of the strontium titanate particles preferably satisfy the following formula (2a), and more preferably satisfy the following formula (2b). N>M···(2) 80%>NM>20% (2a) 50%>NM>30% (2b)

[0035] The detachment rate M of the spacer particles is preferably 3% or more and 40% or less, and more preferably 15% or more and 30% or less. By making the detachment rate M of the spacer particles 3% or more, it is possible to suppress a decrease in the fluidity of the toner caused by the spacer particles adhering to the toner base particles. By making the detachment rate M of the spacer particles 50% or less, the developer of this embodiment is more likely to satisfy the above formula (2).

[0036] The detachment rate N of the strontium titanate particles is preferably 40% or more and 97% or less, and more preferably 50% or more and 70% or less. By setting the detachment rate N of the strontium titanate particles to 40% or more, the developer of this embodiment is more likely to satisfy the above-mentioned formula (2). By setting the detachment rate N of the strontium titanate particles to 97% or less, the developer of this embodiment can exhibit even better image density stability and can further appropriately suppress the occurrence of fogging.

[0037] The coverage rate A of the spacer particles on the toner particles, the coverage rate B of the strontium titanate particles on the carrier particles, the detachment rate M of the spacer particles, and the detachment rate N of the strontium titanate particles can be measured by the method described in the examples or a method based thereon.

[0038] [Carrier particles] The carrier particles include carrier base particles and strontium titanate particles attached to the surfaces of the carrier base particles.

[0039] (Carrier mother particles) The carrier base particle includes a carrier core and a coating layer that covers the surface of the carrier core.

[0040] (Career Core) The carrier core preferably contains a magnetic material. The carrier core may be a particle of a magnetic material, or may be a particle including a carrier core binder resin and particles of a magnetic material dispersed in the carrier core binder resin (hereinafter, may be referred to as a resin carrier core).

[0041] Examples of the magnetic material contained in the carrier core include ferromagnetic metals (more specifically, for example, iron, cobalt, nickel, and alloys containing one or more of these metals) and ferromagnetic metal oxides. Examples of the ferromagnetic metal oxide include ferrite and magnetite, which is a type of spinel ferrite. Examples of the ferrite include Ba ferrite, Mn ferrite, Mn-Zn ferrite, Ni-Zn ferrite, Mn-Mg ferrite, Ca-Mg ferrite, Li ferrite, Cu-Zn ferrite, and Mn-Mg-Sr ferrite. Examples of the method for producing the carrier core include a method including a process of crushing and firing a magnetic material. In the production of the carrier core, the saturation magnetization of the carrier can be adjusted by changing the amount of magnetic material added (particularly the ratio of the ferromagnetic material). In the production of the carrier core, the circularity of the carrier core can be adjusted by changing the firing temperature. In addition, the carrier core may be a commercially available product.

[0042] Examples of magnetic material particles used as carrier cores include ferrite particles. Ferrite particles tend to have sufficient magnetism for image formation using a two-component developer. Ferrite particles manufactured by a general manufacturing method tend not to be perfectly spherical and tend to have moderate irregularities on the surface. When the carrier core is a ferrite particle (ferrite core), from the viewpoint of improving the adhesion between the surface of the ferrite core and the coating layer, the arithmetic mean roughness of the surface of the ferrite core (more specifically, the arithmetic mean roughness Ra defined in JIS (Japanese Industrial Standards) B0601:2013) is preferably 0.3 μm or more and 2.0 μm or less.

[0043] The binder resin in the resin carrier core is preferably a polyester resin, a urethane resin, or a phenol resin, and more preferably a phenol resin. The magnetic material particles in the resin carrier core include, for example, particles containing one or more of the magnetic materials exemplified in the magnetic material.

[0044] In the carrier particles, the mass ratio of the carrier core to the total mass of the carrier core and the coating layer is preferably from 80% by mass to 99% by mass, and more preferably from 95% by mass to 99% by mass.

[0045] The number-average primary particle diameter of the carrier core is preferably 20 μm or more and 60 μm or less. By making the number-average primary particle diameter of the carrier core 20 μm or more, the occurrence of carrier developing can be suppressed. By making the number-average primary particle diameter of the carrier core 60 μm or less, the developability can be optimized.

[0046] The saturation magnetization of the carrier core in an applied magnetic field of 3000 Oe is preferably 60 emu / g or more and 80 emu / g or less. By setting the saturation magnetization of the carrier core to 60 emu / g or more, the occurrence of carrier development can be suppressed. By setting the saturation magnetization of the carrier core to 80 emu / g or less, the developability can be optimized.

[0047] (Coat layer) The coating layer contains a coating resin, barium titanate particles, and carbon black, and has a thickness of, for example, 0.3 μm or more and 2.0 μm or less.

[0048] The mass of the coating layer relative to 100.0 parts by mass of the carrier core is preferably 0.5 parts by mass or more and 10.0 parts by mass or less, more preferably 1.0 parts by mass or more and 3.0 parts by mass or less. By making the mass of the coating layer 0.5 parts by mass or more, the exposure of the carrier core can be suppressed. By making the mass of the coating layer 5.0 parts by mass or less, the carrier can easily charge the toner.

[0049] The coating resin includes a silicone resin. The content of the coating resin in the coating layer is preferably 50.0% by mass or more and 90.0% by mass or less, and more preferably 70.0% by mass or more and 85.0% by mass or less. The content of the silicone resin in the coating resin is preferably 90% by mass or more, and more preferably 100% by mass.

[0050] (Silicone resin) Silicone resin is a resin having a polysiloxane structure (e.g., an alkyl polysiloxane structure). Examples of silicone resins include silicone resins having a methyl group and epoxy resin-modified silicone resins. Examples of silicone resins having a methyl group include silicone resins having a methyl group and no phenyl group (hereinafter sometimes referred to as "methyl silicone resins"), and silicone resins having a methyl group and a phenyl group (hereinafter sometimes referred to as "methyl phenyl silicone resins"). As the silicone resin, methyl silicone resins are preferred.

[0051] (Barium titanate particles) By including barium titanate particles in the coating layer, the carrier can easily impart a desired charge amount to the toner. In addition, by including barium titanate particles in the coating layer, the strength of the coating layer can be optimized, and the strontium titanate particles can be prevented from being embedded in the coating layer.

[0052] The number average primary particle diameter of the barium titanate particles is preferably 100 nm or more and 500 nm or less, more preferably 250 nm or more and 350 nm or less. By making the number average primary particle diameter of the barium titanate particles 100 nm or more, the carrier can more easily impart a desired charge amount to the toner. By making the number average primary particle diameter of the barium titanate particles 500 nm or less, the barium titanate particles can be prevented from being detached from the coating layer.

[0053] In the coating layer, the content of the barium titanate particles relative to 100 parts by mass of the coating resin is preferably 3 parts by mass or more and 50 parts by mass or less, more preferably 15 parts by mass or more and 25 parts by mass or less. By making the content of the barium titanate particles 3 parts by mass or more, the carrier can more easily impart a desired charge amount to the toner. By making the content of the barium titanate particles 50 parts by mass or less, it is possible to suppress the barium titanate particles from being detached from the coating layer.

[0054] (Carbon Black) Carbon black promotes the migration of charges in the coating layer, making it easier for the carrier to impart a desired amount of charge to the toner.

[0055] The number-average primary particle diameter of the carbon black is preferably 10 nm or more and 200 nm or less, more preferably 20 nm or more and 60 nm or less. By making the number-average primary particle diameter of the carbon black 10 nm or more, the carrier can more easily impart a desired charge amount to the toner. By making the number-average primary particle diameter of the carbon black 200 nm or less, it is possible to suppress the carbon black from being detached from the coating layer.

[0056] In the coating layer, the content of carbon black relative to 100 parts by mass of the coating resin is preferably 3 parts by mass or more and 20 parts by mass or less, more preferably 5 parts by mass or more and 12 parts by mass or less. By making the content of carbon black 3 parts by mass or more, the carrier can more easily impart a desired charge amount to the toner. By making the content of carbon black 20 parts by mass or less, it is possible to suppress the carbon black from being detached from the coating layer.

[0057] (Other ingredients) The coating layer may further contain other components in addition to the coating resin, the barium titanate particles, and the carbon black, such as a charge control agent, an adhesion improver, and a crosslinking agent.

[0058] (Strontium titanate particles) Strontium titanate particles have a moderately high dielectric constant, and are therefore preferred as particles to be attached to the surface of the carrier base particle. The strontium titanate particles may be doped. When the strontium titanate particles are doped, the amount of the doped element may be 1.00% by mass or less, 0.10% by mass or less, or less than 0.01% by mass, based on the total mass of the strontium titanate particles. However, the strontium titanate particles may not be doped. As the strontium titanate particles, non-doped strontium titanate is preferred.

[0059] The number average primary particle diameter of the strontium titanate particles is preferably 15 nm or more and 100 nm or less, more preferably 25 nm or more and 40 nm or less. By making the number average primary particle diameter of the strontium titanate particles 15 nm or more, it is possible to prevent the strontium titanate particles from being embedded in the coating layer. By making the number average primary particle diameter of the strontium titanate particles 100 nm or less, it is possible to prevent the strontium titanate particles from being detached from the coating layer.

[0060] From the viewpoint of forming an image having a desired image density and little fog, the amount of strontium titanate particles is preferably 0.01 parts by mass or more and 0.20 parts by mass or less, more preferably 0.01 parts by mass or more and 0.06 parts by mass or less, and even more preferably 0.03 parts by mass or more and 0.06 parts by mass or less, relative to 100.00 parts by mass of the carrier base particles.

[0061] (Carrier Manufacturing Method) The method for producing the carrier includes, for example, a step of forming carrier base particles and a step of adding an external additive to the carrier base particles.

[0062] (Carrier mother particle formation process) In this step, a coating liquid is applied to the surface of the carrier core. The coating liquid contains a coating resin, barium titanate particles, carbon black, and a solvent. The solid content of the coating liquid is preferably 10% by mass or more and 30% by mass or less.

[0063] Examples of the solvent for the coating liquid include lactam compounds (e.g., 2-pyrrolidone and N-methyl-2-pyrrolidone), ketone compounds (e.g., methyl ethyl ketone and methyl isobutyl ketone), cyclic ether compounds (e.g., tetrahydrofuran and tetrahydropyran), alcohol compounds (e.g., normal butanol and isobutanol), ester solvents (e.g., ethyl acetate and isobutyl acetate), and aromatic hydrocarbon compounds (e.g., toluene and xylene).Toluene is preferred as the solvent for the coating liquid.

[0064] Examples of methods for applying the coating liquid to the surface of the carrier core include a method of immersing the carrier core in the coating liquid and a method of spraying the coating liquid onto the carrier core in the fluidized bed. In the method of immersing the carrier core in the coating liquid, a small amount of the coating liquid is applied to the convex parts of the surface of the carrier core, while a large amount of the coating liquid is applied to the concave parts of the surface of the carrier core, so the amount of the coating liquid tends to be uneven. In contrast, in the method of spraying the coating liquid onto the carrier core in the fluidized bed, the coating liquid tends to be applied uniformly to both the convex parts and the concave parts of the surface of the carrier core. From the above, the method of spraying the coating liquid onto the carrier core in the fluidized bed is preferred as the method for applying the coating liquid onto the surface of the carrier core.

[0065] In this process, the carrier cores after the coating process are heated to remove the solvent contained in the coating liquid. If the coating liquid contains an uncured coating resin, the uncured coating resin is thermally cured. As a result, a coating layer is formed from the coating liquid. The heating temperature during heating is preferably 100°C or higher and 300°C or lower, more preferably 180°C or higher and 220°C or lower. The heating time during heating is preferably 30 minutes or higher and 90 minutes or lower, more preferably 50 minutes or higher and 70 minutes or lower.

[0066] (External addition process to carrier base particles) In this step, for example, a mixer is used to mix the carrier base particles and the strontium titanate particles. By mixing, the strontium titanate particles are attached to the surface of the carrier base particles, and a carrier containing the carrier particles is obtained. The mixing in the external addition step to the carrier base particles is preferably carried out under conditions in which the strontium titanate particles are not completely embedded in the carrier base particles. When the external addition step is carried out using a rocking mixer (registered trademark), the mixing time is preferably 5 minutes or more and 25 minutes or less, more preferably 12 minutes or more and 18 minutes or less.

[0067] [Toner particles] The toner particles include toner base particles and an external additive that adheres to the surface of the toner base particles.

[0068] (External additives) The external additive adheres to the surface of the toner base particle. The external additive includes spacer particles and base silica particles. The external additive may further include other particles (hereinafter, other external additive particles) other than the spacer particles and base silica particles. The total content of the spacer particles and base silica particles in the external additive is preferably 60% by mass or more and 90% by mass or less.

[0069] (Spacer particles) The number-average primary particle diameter of the spacer particles is 35 nm or more and 200 nm or less, preferably 45 nm or more and 140 nm or less, more preferably 65 nm or more and 120 nm or less, and even more preferably 90 nm or more and 110 nm or less. By making the number-average primary particle diameter of the spacer particles 35 nm or more, the function of the spacer particles can be effectively exhibited. By making the number-average primary particle diameter of the spacer particles 200 nm or less, the detachment of the spacer particles from the toner base particles can be effectively suppressed.

[0070] The number-average primary particle size of the spacer particles is preferably larger than the number-average primary particle size of the strontium titanate particles, which can effectively prevent the strontium titanate particles from coming into contact with the base silica particles.

[0071] Examples of the spacer particles include silica particles (hereinafter, the silica particles used as the spacer particles may be referred to as "spacer silica particles"), resin particles, aluminum oxide particles, magnesium oxide particles, zinc oxide particles, and composite particles combining these. As the spacer particles, spacer silica particles or resin particles are preferred, and resin particles are more preferred. By using resin particles as the spacer particles, the melting property of the toner can be optimized.

[0072] The resin contained in the spacer particles is preferably a styrene-(meth)acrylic resin. The content of the styrene-(meth)acrylic resin in the spacer particles is preferably 70% by mass or more, more preferably 95% by mass or more, and even more preferably 100% by mass.

[0073] Styrene-(meth)acrylic resin is a copolymer of a styrene compound and a (meth)acrylic acid compound. Examples of the (meth)acrylic acid compound include (meth)acrylic acid, (meth)acrylonitrile, and (meth)acrylic acid alkyl esters (particularly, (meth)acrylic acid alkyl esters having an alkyl group having 1 to 4 carbon atoms in the ester moiety). As the (meth)acrylic acid compound, (meth)acrylic acid alkyl esters are preferred.

[0074] Examples of the styrene compound include styrene, alkylstyrenes (more specifically, α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, ethylstyrene, 2,3-dimethylstyrene, 2,4-dimethylstyrene, o-tert-butylstyrene, m-tert-butylstyrene, and p-tert-butylstyrene), and halogenated styrenes (more specifically, α-chlorostyrene, o-chlorostyrene, m-chlorostyrene, and p-chlorostyrene). As the styrene compound, styrene is preferred.

[0075] The content of the first repeating unit derived from a styrene compound relative to all repeating units contained in the styrene-(meth)acrylic resin is preferably from 5.0% by mass to 50.0% by mass, and more preferably from 15.0% by mass to 25.0% by mass.

[0076] Examples of the (meth)acrylic acid alkyl ester include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, iso-propyl (meth)acrylate, butyl (meth)acrylate (specifically, n-butyl (meth)acrylate), iso-butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. As the (meth)acrylic acid alkyl ester, butyl (meth)acrylate is preferred.

[0077] The content ratio of the second repeating unit derived from the (meth)acrylic acid compound relative to all repeating units contained in the styrene-(meth)acrylic resin is preferably 20.0 mass % or more and 60.0 mass % or less, and more preferably 35.0 mass % or more and 45.0 mass % or less.

[0078] From the viewpoint of imparting an appropriate rigidity to the spacer particle, it is preferable that the styrene-(meth)acrylic resin further has a third repeating unit derived from a crosslinking agent. That is, it is preferable that the styrene-(meth)acrylic resin is a crosslinked styrene-(meth)acrylic resin having a first repeating unit derived from a styrene compound, a second repeating unit derived from a (meth)acrylic acid compound, and a third repeating unit derived from a crosslinking agent.

[0079] Examples of the crosslinking agent include compounds having two or more vinyl groups.Specific examples of the crosslinking agent include N,N'-methylenebisacrylamide, divinylbenzene, ethylene glycol diacrylate, ethylene glycol dimethacrylate, diethylene glycol diacrylate, tetraethylene glycol diacrylate, polyethylene glycol diacrylate, 1,4-butanediol diacrylate, 1,6-hexanediol diacrylate, tripropylene glycol diacrylate, trimethylolpropane triacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, 1,4-butanediol dimethacrylate, and 1,6-hexanediol dimethacrylate.As the crosslinking agent, divinylbenzene is preferable.

[0080] The content ratio of the third repeating unit relative to the total repeating units of the styrene-(meth)acrylic resin is preferably 20.0% by mass or more and 60.0% by mass or less, more preferably 35.0% by mass or more and 45.0% by mass or less. By making the content ratio of the third repeating unit 20.0% by mass or more, the spacer particles are given an appropriate rigidity, and the spacer particles can more easily perform their function as spacers. By making the content ratio of the third repeating unit 60.0% by mass or less, the rigidity of the spacer particles becomes excessively high, and it is possible to suppress abrasion of the surface of the photoreceptor.

[0081] The crosslinked resin preferably has a repeating unit derived from styrene, a repeating unit derived from butyl methacrylate, and a repeating unit derived from divinylbenzene.

[0082] From the viewpoint of fully exerting the function of the spacer particles while suppressing detachment from the toner mother particles, the content of the spacer particles in the toner particles is preferably 0.10 parts by mass or more and 5.00 parts by mass or less, more preferably 0.40 parts by mass or more and 2.20 parts by mass or less, and even more preferably 0.80 parts by mass or more and 1.50 parts by mass or less, relative to 100.00 parts by mass of the toner mother particles. By making the content of the spacer particles 0.10 parts by mass or more, it becomes easy to fully exert the function as the spacer particles. By making the content of the spacer particles 5.00 parts by mass or less, it is possible to suppress the spacer particles from being detached from the toner mother particles.

[0083] When the spacer particles are resin particles, the resin particles can be produced by known methods (e.g., suspension polymerization and phase inversion emulsification). Polymerization initiators used in the production of resin particles include, for example, inorganic peroxides (e.g., potassium persulfate, ammonium persulfate, and hydrogen peroxide), organic peroxides (e.g., t-butyl peroxide, cumene hydroxyperoxide, and paramenthane peroxide), and azo compounds (e.g., azobisdiisobutylnitrile and 2,2'-azobis(2-amidinopropane)dihydrochloride), and inorganic peroxides or organic peroxides are preferred.

[0084] When the spacer particles are spacer silica particles, the spacer silica particles can be produced, for example, by a dry method. The spacer silica particles may be subjected to at least one of a positive charging treatment and a hydrophobic treatment by a surface treatment agent.

[0085] (Base silica particles) The base silica particles are preferably silica particles that have been subjected to a surface treatment to impart hydrophobicity. The number-average primary particle diameter of the base silica particles is preferably 10 nm or more and 30 nm or less, more preferably 15 nm or more and 25 nm or less. By making the number-average primary particle diameter of the base silica particles 10 nm or more, it is possible to prevent the base silica particles from being embedded in the toner mother particles. In addition, by making the number-average primary particle diameter of the base silica particles 30 nm or less, it is possible to prevent the base silica particles from being detached from the toner mother particles.

[0086] In order to fully exert the function of the base silica particles while suppressing detachment from the toner base particles, the content of the base silica particles in the toner particles is preferably 0.10 parts by mass or more and 10.00 parts by mass or less, and more preferably 0.50 parts by mass or more and 2.50 parts by mass or less, per 100.00 parts by mass of the toner base particles.

[0087] (Other external additive particles) As the other external additive particles, metal oxide particles (more specifically, aluminum oxide particles, titanium oxide particles, magnesium oxide particles, and zinc oxide particles) are preferred, and aluminum oxide particles are more preferred. The number average primary particle size of the aluminum oxide particles is preferably 5 nm or more and 50 nm or less, and more preferably 10 nm or more and 20 nm or less.

[0088] The content of the other external additives is preferably from 0.10 parts by mass to 5.00 parts by mass, and more preferably from 0.50 parts by mass to 1.00 parts by mass, relative to 100.00 parts by mass of the toner base particles, from the viewpoint of suppressing detachment from the toner base particles while fully exerting its function.

[0089] However, it is preferable that the toner particles do not contain titanic acid compound particles (e.g., barium titanate particles and strontium titanate particles) as an external additive. Specifically, the content of titanic acid compound particles in the external additive is preferably 3% by mass or less, more preferably 0% by mass.

[0090] (Toner base particles) The toner base particles contain, for example, a binder resin and at least one selected from the group consisting of a colorant, a charge control agent, and a release agent. In the toner base particles, the content of the binder resin is preferably 70% by mass or less and 97% by mass or less, and more preferably 80% by mass or more and 93% by mass or less. The binder resin, the colorant, the charge control agent, and the release agent will be described below.

[0091] (Binding resin) In order to obtain a toner having excellent low-temperature fixing properties, the toner base particles preferably contain a thermoplastic resin as a binder resin, and more preferably contain a thermoplastic resin at a ratio of 85% by mass or more of the total binder resin. Examples of the thermoplastic resin include polyester resin, styrene resin, acrylic acid ester resin (more specifically, acrylic acid ester polymer, methacrylic acid ester polymer, etc.), olefin resin (more specifically, polyethylene resin, polypropylene resin, etc.), vinyl resin (more specifically, vinyl chloride resin, polyvinyl alcohol, vinyl ether resin, N-vinyl resin, etc.), polyamide resin, and urethane resin. In addition, copolymers of these resins, that is, copolymers in which any repeating unit is introduced into the above resin (more specifically, styrene-acrylic resin, styrene-butadiene resin, etc.) can also be used as the binder resin.

[0092] The binder resin is preferably a polyester resin. The polyester resin is a polymer of one or more polyhydric alcohol monomers and one or more polycarboxylic acid monomers. Instead of the polycarboxylic acid monomer, a polycarboxylic acid derivative (more specifically, a polycarboxylic acid anhydride, a polycarboxylic acid halide, etc.) may be used.

[0093] Examples of polyhydric alcohol monomers include diol monomers, bisphenol monomers, and trihydric or higher alcohol monomers.

[0094] Diol monomers include, for example, ethylene glycol, diethylene glycol, triethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, neopentyl glycol, 2-butene-1,4-diol, 1,5-pentanediol, 1,6-hexanediol, 1,4-cyclohexanedimethanol, 1,4-benzenediol, dipropylene glycol, polyethylene glycol, polypropylene glycol, and polytetramethylene glycol.

[0095] Examples of bisphenol monomers include bisphenol A, hydrogenated bisphenol A, ethylene oxide adducts of bisphenol A, and propylene oxide adducts of bisphenol A.

[0096] Examples of trihydric or higher alcohol monomers include sorbitol, 1,2,3,6-hexanetetrol, 1,4-sorbitan, pentaerythritol, dipentaerythritol, tripentaerythritol, 1,2,4-butanetriol, 1,2,5-pentanetriol, glycerol, diglycerol, 2-methylpropanetriol, 2-methyl-1,2,4-butanetriol, trimethylolethane, trimethylolpropane, and 1,3,5-trihydroxymethylbenzene.

[0097] Examples of polycarboxylic acid monomers include dicarboxylic acid monomers and tricarboxylic or higher carboxylic acid monomers.

[0098] Examples of divalent carboxylic acid monomers include maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, phthalic acid, isophthalic acid, terephthalic acid, 5-sulfoisophthalic acid, 5-sodium sulfoisophthalate, cyclohexanedicarboxylic acid, adipic acid, sebacic acid, azelaic acid, malonic acid, succinic acid, alkyl succinic acid, and alkenyl succinic acid. Examples of alkyl succinic acid include n-butyl succinic acid, isobutyl succinic acid, n-octyl succinic acid, n-dodecyl succinic acid, and isododecyl succinic acid. Examples of alkenyl succinic acid include n-butenyl succinic acid, isobutenyl succinic acid, n-octenyl succinic acid, n-dodecenyl succinic acid, and isododecenyl succinic acid.

[0099] Examples of trivalent or higher carboxylic acid monomers include 1,2,4-benzenetricarboxylic acid (trimellitic acid), 2,5,7-naphthalenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, 1,2,4-butanetricarboxylic acid, 1,2,5-hexanetricarboxylic acid, 1,3-dicarboxyl-2-methyl-2-methylenecarboxypropane, 1,2,4-cyclohexanetricarboxylic acid, tetra(methylenecarboxyl)methane, 1,2,7,8-octanetetracarboxylic acid, pyromellitic acid, and empol trimer acid.

[0100] The polyester resin is preferably a polymer of a bisphenol monomer, a divalent carboxylic acid monomer, and a trivalent carboxylic acid monomer, and more preferably a polymer of a bisphenol A alkylene oxide adduct, terephthalic acid, isophthalic acid, and trimellitic acid.

[0101] The polyester resin is preferably an amorphous polyester resin. For amorphous polyester resins, it is often impossible to measure a clear melting point. Therefore, a polyester resin that does not show a clear endothermic peak in an endothermic curve measured using a differential scanning calorimeter may be judged to be an amorphous polyester resin.

[0102] The softening point (Tm) of the polyester resin is preferably 70° C. or more and 130° C. or less, and more preferably 90° C. or more and 110° C. or less. By setting the softening point of the polyester resin to 70° C. or more, it is possible to impart excellent hot offset resistance to the toner. By setting the softening point of the polyester resin to 130° C. or less, it is possible to impart excellent low-temperature fixing property to the toner.

[0103] The glass transition point (Tg) of the polyester resin is preferably 30° C. or higher and 80° C. or lower, and more preferably 40° C. or higher and 60° C. or lower. By setting the glass transition point of the polyester resin to 30° C. or higher, it is possible to impart excellent heat-resistant storage stability to the toner. By setting the glass transition point of the polyester resin to 100° C. or lower, it is possible to impart excellent low-temperature fixing property to the toner.

[0104] (Coloring agent) As the colorant, a known pigment or dye can be used in accordance with the color of the toner, and examples of the colorant include a black colorant, a yellow colorant, a magenta colorant, and a cyan colorant.

[0105] An example of the black colorant is carbon black. The black colorant may be a colorant that is toned to black using a yellow colorant, a magenta colorant, and a cyan colorant.

[0106] In the toner base particles, the content of the colorant is preferably from 1 to 20 parts by mass, and more preferably from 3 to 7 parts by mass, relative to 100 parts by mass of the binder resin.

[0107] (Charge control agent) The charge control agent is used, for example, for the purpose of obtaining a toner having excellent charge stability and charge rise characteristics. The charge rise characteristics of the toner are an index of whether the toner can be charged to a predetermined charge level in a short time. Examples of the charge control agent include a positive charge control agent and a negative charge control agent. The cationic property (positive chargeability) of the toner can be strengthened by adding a positive charge control agent to the toner base particles, and the anionic property (negative chargeability) of the toner can be strengthened by adding a negative charge control agent to the toner base particles. Examples of the positive charge control agent include pyridine, nigrosine, and quaternary ammonium salts. Examples of the negative charge control agent include metal-containing azo dyes, sulfo group-containing resins, oil-soluble dyes, naphthenic acid metal salts, acetylacetone metal complexes, salicylic acid metal complexes, boron compounds, fatty acid soaps, and long-chain alkyl carboxylates. However, if sufficient chargeability is ensured in the toner, it is not necessary to add a charge control agent to the toner base particles. In the toner base particles, the content of the charge control agent is preferably from 0.1 to 5 parts by mass, and more preferably from 0.5 to 2 parts by mass, relative to 100 parts by mass of the binder resin.

[0108] (Release agent) The release agent is used, for example, for the purpose of obtaining a toner having excellent hot offset resistance. Examples of the release agent include aliphatic hydrocarbon waxes, oxides of aliphatic hydrocarbon waxes, plant-derived waxes, animal-derived waxes, mineral-derived waxes, ester waxes mainly composed of fatty acid esters, and waxes in which fatty acid esters are partially or completely deoxidized. Examples of the aliphatic hydrocarbon waxes include polyethylene waxes (e.g., low molecular weight polyethylene), polypropylene waxes (e.g., low molecular weight polypropylene), polyolefin copolymers, polyolefin waxes, microcrystalline waxes, paraffin waxes, and Fischer-Tropsch waxes. Examples of the oxides of aliphatic hydrocarbon waxes include oxidized polyethylene waxes and block copolymers of oxidized polyethylene waxes. Examples of the plant-derived waxes include candelilla wax, carnauba wax, Japan wax, jojoba wax, and rice wax. Examples of the animal-derived waxes include beeswax, lanolin, and spermaceti. Examples of the mineral-derived waxes include ozokerite, ceresin, and petrolatum. Examples of ester waxes mainly composed of fatty acid ester include Montan acid ester wax and castor wax. Examples of waxes in which fatty acid ester is partially or completely deoxidized include deoxidized carnauba wax. In the toner base particles, the content of the release agent is preferably 1 part by mass or more and 20 parts by mass or less, more preferably 3 parts by mass or more and 10 parts by mass or less, based on 100 parts by mass of the binder resin.

[0109] The toner particles may further contain known additives as necessary. The volume median diameter of the toner particles is preferably 4.0 μm or more and 12.0 μm or less. The volume median diameter of the toner base particles is preferably 4.0 μm or more and 12.0 μm or less, and more preferably 5.0 μm or more and 9.0 μm or less. The toner particles are preferably non-magnetic toner.

[0110] (Toner manufacturing method) An example of a toner manufacturing method will be described. The toner manufacturing method includes a toner base particle preparation step of preparing toner base particles, and an external additive step of attaching an external additive to the surface of the toner base particles. The external additive includes spacer particles and base silica particles.

[0111] (Toner base particle preparation process) In the toner base particle preparation step, the toner base particles are prepared by, for example, a pulverization method or an aggregation method. In the toner base particle preparation step, the toner base particles are preferably prepared by a pulverization method. That is, in the toner, the toner base particles are preferably pulverized toner base particles.

[0112] In one example of the pulverization method, first, a binder resin is mixed with other components added as necessary. The resulting mixture is then melt-kneaded using a melt-kneading device (e.g., a single-screw or twin-screw extruder). The resulting melt-kneaded product is then pulverized and classified. This produces toner base particles.

[0113] In one example of the aggregation method, first, in an aqueous medium containing fine particles of a binder resin and other components added as necessary, these fine particles are aggregated until they reach a desired particle size. This forms aggregated particles containing the binder resin and the like. The resulting aggregated particles are then heated to unify the components contained in the aggregated particles. This gives toner base particles.

[0114] (External addition process) In this process, the external additive is attached to the surface of the toner base particle. For example, a method of attaching the external additive to the surface of the toner base particle may be used to mix the toner base particle and the external additive particle while stirring them using a mixer. When the external addition process is performed using an FM mixer, the mixing time is preferably 6 minutes or more and 25 minutes or less, more preferably 8 minutes or more and 15 minutes or less.

[0115] Second embodiment: Image forming apparatus The second embodiment of the present invention relates to an image forming apparatus. The image forming apparatus of this embodiment includes the developer of the first embodiment, a photoconductor, a charging device that charges the surface of the photoconductor, and a developing device that supplies toner to the surface of the photoconductor and develops it into a toner image. The above-mentioned printing durability test is performed using the image forming apparatus. The image forming apparatus of this embodiment uses the developer of the first embodiment, and therefore has excellent image density stability and can suppress the occurrence of fogging.

[0116] An image forming apparatus 40, which is an example of the image forming apparatus of this embodiment, will be described below with reference to Fig. 2. The image forming apparatus 40 shown in Fig. 2 includes developers (developer D in use and replenishment developer E, see Fig. 3), photoconductors 41a to 41d, charging devices 42a to 42d, an exposure device 43, developing devices 44a to 44d, a transfer device 45, a fixing device 46, a cleaning device 47, and a control unit 48. Hereinafter, unless there is a need to distinguish between them, each of the photoconductors 41a to 41d will be referred to as a photoconductor 41, each of the charging devices 42a to 42d will be referred to as a charging device 42, and each of the developing devices 44a to 44d will be referred to as a developing device 44.

[0117] The developer in use D includes an initial developer and a replenishment developer E. The initial developer and the replenishment developer E are each the developer of the first embodiment.

[0118] The photoreceptor 41 is cylindrical. The photoreceptor 41 has a metal cylinder (e.g., a cylindrical conductive substrate) as a core material. A photosensitive layer is provided on the outside of the core material. The photoreceptor 41 is supported so as to be rotatable. The photoreceptor 41 is driven to rotate by, for example, a motor (not shown).

[0119] The charging device 42 charges the peripheral surface of the photoconductor 41 .

[0120] The exposure device 43 exposes the charged peripheral surface of the photoreceptor 41 to light, thereby forming an electrostatic latent image on the peripheral surface of the photoreceptor 41. For example, an electrostatic latent image is formed on the surface layer portion (photosensitive layer) of the photoreceptor 41 based on image data.

[0121] The developing device 44 develops the electrostatic latent image with the in-use developer D. More specifically, the developing device 44 develops the electrostatic latent image formed on the peripheral surface of the photoconductor 41 with the in-use developer D, and develops the electrostatic latent image into a toner image. Details of the developing device 44 will be described later.

[0122] The transfer device 45 includes a transfer belt 51, a drive roller 52, a driven roller 53, a tension roller 54, primary transfer rollers 55a to 55d, and a secondary transfer roller 56. Hereinafter, when there is no need to distinguish between them, each of the primary transfer rollers 55a to 55d will be referred to as a primary transfer roller 55. The transfer belt 51 is an endless belt stretched around the drive roller 52, the driven roller 53, and the tension roller 54. As the drive roller 52 rotates, the transfer belt 51 is transported in the clockwise direction in FIG. 2 (the direction of the arrow d1 in FIG. 2). As the transfer belt 51 is transported, the driven roller 53 and the tension roller 54 are driven to rotate.

[0123] After the toner images are formed on the photoconductors 41a to 41d, a bias (voltage) is applied to the primary transfer rollers 55a to 55d, whereby the toner attached to the photoconductors 41a to 41d is sequentially primarily transferred onto the transfer belt 51. In this manner, toner images of multiple colors are superimposed on the transfer belt 51. After the primary transfer, a bias (voltage) is applied to the secondary transfer roller 56, whereby the toner images of multiple colors on the transfer belt 51 are secondarily transferred onto the recording medium P (for example, printing paper) being conveyed. Then, the toner images of multiple colors superimposed on the transfer belt 51 are secondarily transferred collectively onto the recording medium P. In this manner, an image composed of unfixed toner is formed on the recording medium P.

[0124] After the secondary transfer, the fixing device 46 heats and pressurizes the toner on the recording medium P to fix the toner to the recording medium P. In this manner, an image made of the fixed toner is formed on the recording medium P.

[0125] The cleaning device 47 cleans the toner remaining on the transfer belt 51 after the secondary transfer.

[0126] The control unit 48 electronically controls the operation of the image forming apparatus 40 based on the outputs of various sensors. The control unit 48 includes, for example, a central processing unit (CPU), a random access memory (RAM), and a storage device that stores programs and rewritably stores predetermined data. A user gives instructions (for example, electrical signals) to the control unit 48 through an input unit (not shown). The input unit is, for example, a keyboard, a mouse, or a touch panel.

[0127] Next, the developing device 44 will be described in more detail with reference to FIG. 3. FIG. 3 shows the developing device 44 and its surroundings of the image forming apparatus 40 shown in FIG. 2. The developing device 44 has at least a container 114. The developing device 44 further has a developer carrier 111, a regulating blade 112, a plurality of stirring shafts 113, a supply section 115, and a discharge section 116. The developing device 44 has the container 114, the supply section 115, and the discharge section 116, and is a so-called trickle development type developing device 44.

[0128] The storage section 114 stores the in-use developer D and a plurality of stirring shafts 113. The in-use developer D stored in the storage section 114 includes an initial developer. The plurality of stirring shafts 113 include a first stirring shaft 113a and a second stirring shaft 113b. The first stirring shaft 113a has a spiral stirring blade. The second stirring shaft 113b has a spiral stirring blade that faces in the opposite direction (opposite phase) to the spiral blade of the first stirring shaft 113a. The first stirring shaft 113a stirs the in-use developer D in the storage section 114, and transports the in-use developer D in a first transport direction (a direction perpendicular to the paper surface of FIG. 3 and a direction from the back to the front of the paper surface) from one end side to the other end side in the axial direction of the developer carrier 111. The second agitating shaft 113b transports the in-use developer D in a second transport direction opposite to the first transport direction while agitating the in-use developer D in the storage section 114. As the in-use developer D, which contains toner and carrier, is agitated, the toner is charged by friction with the carrier, and the charged toner is carried by the carrier. The second agitating shaft 113b supplies the in-use developer D to the developer carrier 111 while transporting the in-use developer D in the second transport direction.

[0129] The replenishing section 115 is provided above the containing section 114. The replenishing section 115 replenishing the replenishing developer E to the containing section 114. The replenishing section 115 has a replenishing amount adjusting member 115a and a developer container 115b.

[0130] The supply amount adjustment member 115a controls the supply amount of the replenishment developer E supplied from the developer container 115b to the storage portion 114. The supply amount adjustment member 115a is composed of, for example, a screw shaft whose rotation operation is controlled by the control portion 48. For example, the supply amount of the replenishment developer E can be changed according to the amount of rotation of the screw shaft.

[0131] The developer container 115b accommodates the replenishment developer E. The replenishment developer E in the developer container 115b is supplied to the accommodation portion 114.

[0132] The discharge section 116 discharges the developer D in use from the storage section 114. The discharge section 116 includes a discharge path 116a and a collection container 116b. The discharge path 116a connects the storage section 114 and the collection container 116b. When the amount of the developer D in use in the storage section 114 exceeds a predetermined amount, the excess developer D in use enters the discharge path 116a from the opening on the upper end side of the discharge path 116a. The predetermined amount is, for example, an amount determined by the upper end position of the discharge path 116a. The excess developer D in use is, for example, the amount of developer D in use that exceeds the predetermined amount. When the excess developer D in use enters the discharge path 116a, it advances downward inside the discharge path 116a by gravity and flows into the collection container 116b. Then, the collection container 116b stores the excess developer D in use. Hereinafter, the collected developer is referred to as a collected developer F.

[0133] In the image forming apparatus 40 before starting image formation (for example, an unused image forming apparatus 40), the developer D in use accommodated in the accommodation portion 114 is an initial developer.

[0134] After image formation is started, before the replenishing unit 115 replenishes the replenishment developer E into the storage unit 114, the developer D in use contained in the storage unit 114 is the initial developer. In the storage unit 114, the initial developer is stirred by the stirring shaft 113, and the toner particles 4 contained in the initial developer are triboelectrically charged. Then, the stirred initial developer is carried on the developer carrier 111.

[0135] As printing by the image forming device 40 continues, the replenishment developer E is replenished into the storage unit 114, and the used developer D is discharged from the storage unit 114. Therefore, as printing by the image forming device 40 continues, the used developer D stored in the storage unit 114 is gradually replaced with the replenishment developer E replenished from the replenishing unit 115. After the replenishing unit 115 replenishes the replenishment developer E into the storage unit 114, the initial developer and the replenishment developer E are stirred by the stirring shaft 113 in the storage unit 114, and the toner particles 4 contained in the initial developer and the toner particles 4 contained in the replenishment developer E are triboelectrically charged. Then, the stirred initial developer and the replenishment developer E are carried on the developer carrying member 111.

[0136] The developer carrier 111 is disposed near the photoconductor 41. The developer carrier 111 includes a magnet roll and a developing sleeve. The magnet roll has magnetic poles at least on its surface. The magnetic poles are, for example, N and S poles based on permanent magnets. The developing sleeve is a non-magnetic cylinder (for example, an aluminum pipe). The magnet roll is located inside the developing sleeve (inside the cylinder), and the developing sleeve is located on the surface of the developer carrier 111. The shaft of the magnet roll and the developing sleeve are connected via a flange so that the developing sleeve can rotate around the non-rotating magnet roll.

[0137] As already described, the charged toner is carried by the carrier in the storage section 114. The developer carrier 111 (specifically, the developing sleeve) attracts the carrier in the storage section 114 by magnetic force while rotating in the clockwise direction in FIG. 3 (the direction of the arrow d2 in FIG. 3), and carries the carrier carrying the toner (i.e., the developer in use D) on its circumferential surface. Then, a magnetic brush is formed by the developer in use D carried by the developer carrier 111.

[0138] The regulating blade 112 regulates the thickness of the magnetic brush of the developer D in use formed on the circumferential surface of the developer carrier 111 to a predetermined thickness.

[0139] After the thickness of the magnetic brush is regulated by the regulating blade 112, the developer carrier 111 (specifically, the developing sleeve) further rotates in the clockwise direction (the direction of the arrow d2 in FIG. 3), and the in-use developer D is transported to the closest portion N between the photoconductor 41 and the developer carrier 111. The photoconductor 41 rotates in the counterclockwise direction in FIG. 3 (the direction of the arrow d3 in FIG. 3). A bias (voltage) is applied to the developer carrier 111, causing a potential difference to occur between the surface potential of the developer carrier 111 and the surface potential of the photoconductor 41. This potential difference causes the toner contained in the in-use developer D carried by the developer carrier 111 to move to the circumferential surface of the photoconductor 41. Specifically, the charged toner contained in the in-use developer D carried on the developer carrier 111 is attracted by an electric force to an electrostatic latent image (for example, an exposed portion where the potential has been lowered by exposure to light compared to a non-exposed portion) formed on the photoreceptor 41, and moves to the electrostatic latent image on the photoreceptor 41. As a result, a toner image is formed on the surface of the photoreceptor 41.

[0140] The image forming apparatus 40 has been described above with reference to Figs. 2 and 3. However, the image forming apparatus of this embodiment is not limited to the image forming apparatus 40 of Figs. 2 and 3, and can be modified in various ways without departing from the gist of the present invention. For example, some components may be deleted from all the components. Furthermore, the material, shape, dimensions, etc. of each component are merely examples and are not particularly limited, and various modifications are possible. EXAMPLES

[0141] The present invention will be described in more detail below using examples. However, the present invention is not limited to the scope of the examples. In the examples, the longitudinal direction of A4 size printing paper may be referred to as "vertical" and the transverse direction as "horizontal".

[0142] [Measurement of saturation magnetization and coercivity] In this example, the saturation magnetization and coercivity of the carrier core were measured using a high-sensitivity vibrating sample magnetometer ("VSM-P7" manufactured by Toei Kogyo Co., Ltd.) under the condition of an applied magnetic field of 3000 Oe.

[0143] [Measurement of number average primary particle size] The number-average primary particle diameter of the particles was measured using a scanning electron microscope (field emission scanning electron microscope, "JSM-7600F" manufactured by JEOL Ltd.) In measuring the number-average primary particle diameter, the circle-equivalent diameters (Heywood diameter: diameter of a circle having the same area as the projected area of ​​a primary particle) of 100 primary particles were measured, and the number-average value was calculated.

[0144] [Coverage measurement] The coverage rate A of the spacer particles in the toner particles and the coverage rate B of the strontium titanate particles in the carrier particles were measured by the following method. A conductive tape was fixed on a sample stage for SEM with the adhesive surface facing up. The measurement target (toner particles or carrier particles) was scattered on the adhesive surface of this conductive tape. Next, excess measurement target was removed from the adhesive surface by air blowing. Next, a medicine wrapping paper was placed on the adhesive surface, and a load was applied to the measurement target via the medicine wrapping paper, thereby fixing the measurement target to the conductive tape. Next, the medicine wrapping paper was peeled off from the adhesive surface of the conductive tape. As a result, a sample including the conductive tape and the measurement target dispersed and fixed on the adhesive surface of the conductive tape was obtained. A field emission scanning electron microscope (FE-SEM, "JSM-7600F" manufactured by JEOL Ltd.) was used to take a backscattered electron image (surface image) of the surface of the measurement target of the obtained sample. The setting conditions of the FE-SEM were as follows.

[0145] (FE-SEM setting conditions for coverage measurement) Acceleration voltage of electron beam during imaging: 1kV Measurement mode: BE mode (mode that mainly detects backscattered electron signals) ·Magnification: 500x Emission current: 10μA ·Irradiation current: 450pA Shooting mode: Integration (256 times)

[0146] (Image analysis) The obtained image (surface image of the measurement object) was analyzed using image analysis software ("WinROOF" manufactured by Mitani Shoji Co., Ltd.). In the measurement, first, 10 particles were randomly selected from the measurement object. Then, the coverage rate α of each particle (coverage rate A of spacer particles on toner particles or coverage rate B of strontium titanate particles on carrier particles) was measured. The arithmetic average value of the measured coverage rates α of the 10 particles was adopted as the coverage rate of the measurement object.

[0147] (Synthesis of amorphous polyester resin) A 5L reaction vessel equipped with a thermometer (thermocouple), a dehydration tube, a nitrogen introduction tube, and a stirring device (stirring blade) was set in an oil bath. 1575g of BPA-PO (bisphenol A propylene oxide adduct), 163g of BPA-EO (bisphenol A ethylene oxide adduct), 377g of fumaric acid, and 4g of catalyst (dibutyltin oxide) were charged into the reaction vessel. After that, a nitrogen atmosphere was created in the reaction vessel, and the temperature in the reaction vessel was raised to 220°C using an oil bath while stirring the contents.

[0148] The contents of the reaction vessel were polymerized for 8 hours under conditions of nitrogen atmosphere and temperature 220°C while distilling off by-product water. Then, after reducing the pressure in the reaction vessel, the contents of the reaction solution were polymerized for another hour under conditions of reduced pressure atmosphere (pressure: 8 kPa) and temperature 220°C. Then, the temperature in the reaction vessel was lowered to 210°C, and 336 g of trimellitic anhydride was added to the reaction vessel. Then, the contents of the reaction vessel were reacted under conditions of reduced pressure atmosphere (pressure: 8 kPa) and temperature 210°C. The reaction time in the reaction was adjusted so that the softening point (Tm) of the reaction product (amorphous polyester resin) was 100°C and the glass transition point (Tg) was 50°C. Then, the reaction product was taken out of the reaction vessel and cooled to obtain an amorphous polyester resin.

[0149] (Preparation of toner base particles) Using an FM mixer ("FM-10B" manufactured by Nippon Coke & Engineering Co., Ltd.), 100 parts by mass of binder resin, 4 parts by mass of colorant, 1 part by mass of charge control agent, and 5 parts by mass of release agent were mixed. As the binder resin, 100 parts by mass of the above-mentioned amorphous polyester resin (Tm: 100°C, Tg: 50°C) was used. As the colorant, copper phthalocyanine blue pigment (CI Pigment Blue 15:3) was used. As the charge control agent, quaternary ammonium salt ("BONTRON (registered trademark) P-51" manufactured by Orient Chemical Industries Co., Ltd.) was used. As the release agent, carnauba wax ("Special Carnauba Wax No. 1" manufactured by Kato Yoko Co., Ltd.) was used.

[0150] The resulting mixture was melt-kneaded using a twin-screw extruder (Ikegai Corporation, "PCM-30 type"). The resulting melt-kneaded product was pulverized using a mechanical pulverizer (Freund Turbo Corporation, "Turbo Mill"). The pulverized product was classified using a classifier (Nitetsu Mining Co., Ltd., "Elbow Jet"). This resulted in a volume median diameter (D 50 Powdered toner base particles having a particle diameter of 6.8 μm were obtained.

[0151] [Preparation of resin particles] The resin particles (RA) to (RE) were prepared by the following method.

[0152] (Resin particles (RC)) A glass reaction vessel equipped with a thermometer (thermocouple), a stirrer, a reflux condenser, and a nitrogen inlet tube was set in a water bath (set temperature: 80°C). 300.0 parts by mass of ion-exchanged water and 1.0 parts by mass of di-t-butyl peroxide were added to this reaction vessel. Next, the inside of the reaction vessel was placed under a nitrogen gas atmosphere. In the subsequent operations, the temperature of the contents of the reaction vessel was kept at 80°C, and the inside of the reaction vessel was kept under a nitrogen gas atmosphere. Next, while stirring the reaction vessel, 0.2 parts by mass of ammonium persulfate and 60.0 parts by mass of the monomer mixture were dropped into the reaction vessel over 1 hour. The monomer mixture was a mixture of 10 mol% styrene, 40 mol% butyl methacrylate, and 50 mol% divinylbenzene. Next, the contents were reacted while stirring the reaction solution. In this reaction, the reaction temperature (hereinafter sometimes referred to as "temperature T") was 100°C, the reaction time (hereinafter sometimes referred to as "time Y") was 4 hours, and the stirring speed (hereinafter sometimes referred to as "speed Z") was 756 rpm. The reaction solution (emulsion solution) after the reaction was dried to obtain crosslinked resin particles (number average primary particle diameter: 100 nm). These crosslinked resin particles were named resin particles (RC).

[0153] (Resin particles (RA) to (RB) and (RE)) Crosslinked resin particles (resin particles (RA) to (RB) and (RD)) having a number average primary particle diameter of 40 nm, 60 nm or 120 nm were prepared by the same method as in the preparation of the above-mentioned resin particles (RC), except that the temperature X, time Y and speed Z were changed as shown in Table 1. Furthermore, non-crosslinked resin particles (resin particles (RE)) having a number average primary particle diameter of 100 nm were prepared by the same method as in the preparation of the above-mentioned resin particles (RC), except that the amount of monomer used was changed as shown in Table 1. In Table 1, "particle diameter" refers to the number average primary particle diameter.

[0154] [Table 1]

[0155] [Spacer silica particles (Si-A)] Finely ground silica, carbon powder as a reducing agent, and an appropriate amount of water were put into a container and mixed to obtain a mixed material. The mixed material was then heated to about 1800°C in an incinerator to generate SiO2 gas. The generated SiO2 gas was then cooled with cooling air (flow rate: 80 m 3 / hour) to precipitate silica fine particles. The precipitated silica fine particles were then collected using a bag filter. Aminopropylethoxysilane and silicone oil were then added to the collected silica fine particles. The silica fine particles after addition were then subjected to a heat treatment to obtain a solid matter. The solid matter obtained was then crushed using an FM mixer to obtain spacer silica particles (Si-A) with a number-average primary particle diameter of 100 nm.

[0156] [Toner Preparation] (Toner (T-1)) 100.00 parts by mass of the above-mentioned toner base particles, 1.50 parts by mass of base silica particles, 1.26 parts by mass of spacer particles, and 0.75 parts by mass of aluminum oxide particles were mixed for 10 minutes at 4,000 rpm using an FM mixer ("FM-10B" manufactured by Nippon Coke & Engineering Co., Ltd.) (hereinafter, this mixing time will be referred to as external addition time t1). The resulting mixture was sieved using a 200 mesh (75 μm opening) sieve to obtain toner (T-1). As the base silica particles, "AEROSIL (registered trademark) REA90" manufactured by Nippon Aerosil Co., Ltd. (fumed silica with positive charging and hydrophobicity imparted by surface treatment, number average primary particle diameter: 20 nm) was used. As the spacer particles, the above-mentioned resin particles (RC) (number average primary particle diameter: 100 nm) were used. The aluminum oxide particles were "AEROXIDE (registered trademark) Alu C805" (BET specific surface area: 75 to 105 m) manufactured by Nippon Aerosil Co., Ltd. 2 / g, number average primary particle size 13 nm) was used.

[0157] (Toner (T-2)~(T-16)) Toners (T-2) to (T-16) were prepared in the same manner as toner (T-1), except that the type of spacer particles used, the amount used, and the external addition time t1 were changed as shown in Table 2 below. Table 2 below also shows the coverage A of the spacer particles on the toner particles. In Table 2 below, "particle size" indicates the number-average primary particle size of the spacer particles.

[0158] [Table 2]

[0159] [Preparation of carrier] Carriers (C-1) to (C-11) were prepared by the following method.

[0160] (Preparation of Carrier (C-1)) A coating liquid was obtained by mixing 361.2 g of a silicone resin solution ("KR-255" manufactured by Shin-Etsu Chemical Co., Ltd., solid concentration: 50 mass%, solid content: 180.6 g), 36.2 g of barium titanate particles ("BT-03" manufactured by Sakai Chemical Industry Co., Ltd., barium titanate particles produced by a hydrothermal synthesis method, number average primary particle diameter: 304 nm), 14.4 g of carbon black ("Ketjen Black EC-300J" manufactured by Lion Specialty Chemicals Co., Ltd.) and 1444.8 g of toluene using a homomixer.

[0161] Using a fluidized bed coating device (Powrex Corporation, "FD-MP-01 D type"), 5000 g of carrier cores were fluidized while spraying the coating liquid onto the carrier cores. In this way, carrier cores coated with the coating liquid were obtained. The amount of coating liquid used was an amount such that the mass of the coating layer was 1.5 parts by mass (i.e., an amount such that the solid content was 75 g) per 100.0 parts by mass of carrier cores. The coating conditions were an inlet air temperature (corresponding to the predetermined drying temperature described in the embodiment) of 75°C, an inlet air volume of 0.3 m3, and a carrier core diameter of 1.5 mm. 3The conditions were: 1.5 rpm / min, and the rotor rotation speed was 400 rpm. Manganese ferrite cores (manufactured by DOWA IP Creation Co., Ltd., volume median diameter: 40 μm, saturation magnetization: 67 emu / g) were used as carrier cores. The carrier cores coated with the coating liquid were fired at a temperature of 200° C. for 1 hour using an electric furnace. In this way, a coating layer was formed on the surface of the carrier cores, and carrier base particles were obtained.

[0162] 100.00 parts by mass of the above-mentioned carrier base particles and 0.04 parts by mass of strontium titanate particles were mixed for 15 minutes using a rocking mixer (registered trademark) (Aichi Electric Co., Ltd. "RM-10") to attach the strontium titanate particles to the surface of the carrier base particles (hereinafter, the mixing time in the preparation of the carrier is referred to as the external addition time t2). As the strontium titanate particles, non-doped strontium titanate (particle size adjusted product of "SW-100" manufactured by Titan Kogyo Co., Ltd.) with a number average primary particle diameter of 30 nm was used. Thus, carrier (C-1) was obtained.

[0163] (Preparation of Carriers (C-2) to (C-11)) Carriers (C-2) to (C-11) were prepared in the same manner as in the preparation of carrier (C-1), except that the amount of barium titanate particles and the amount of carbon black used in forming the coating layer, the amount of strontium titanate particles used and the number-average primary particle diameter, and the external addition time t2 were changed as shown in Table 3 below. Table 3 below also shows the coverage B of strontium titanate particles on the carrier particles. In Table 3 below, "diameter" indicates the number-average primary particle diameter. "Parts" indicates parts by mass. Specifically, the parts by mass of each component of the coating layer indicates the parts by mass of each component when the amount of the coating resin is 100 parts by mass. The parts by mass of the strontium titanate particles indicates the parts by mass when the amount of the carrier mother particles is 100.00 parts by mass. "BaTiO3" indicates barium titanate particles. "CB" indicates carbon black.

[0164] The strontium titanate particles used in the preparation of carriers (C-2) to (C-11) were all undoped strontium titanate (a particle size adjusted product of "SW-100" manufactured by Titan Kogyo Co., Ltd.). In the preparation of carrier (C-2), no external addition of strontium titanate particles was performed.

[0165] [Table 3]

[0166] <Preparation of Developer> (Developer (D-1)) Using a rocking mixer (registered trademark) (Aichi Electric Co., Ltd. "RM-10"), 8 parts by mass of toner (T-1) and 92 parts by mass of carrier (C-2) were mixed for 30 minutes. This resulted in the initial developer, developer (D-1) (toner concentration: 8% by mass).

[0167] Using a rocking mixer (registered trademark) (Aichi Electric Co., Ltd. "RM-10"), 90 parts by mass of the above toner and 10 parts by mass of the above carrier were mixed for 30 minutes. This resulted in a replenishing developer (carrier concentration: 10% by mass) corresponding to developer (D-1).

[0168] (Developer (D-2)~(D-26)) Except for changing the combination of toner and carrier as shown in Table 4 below, developers (D-2) to (D-26) were prepared in the same manner as developer (D-1). In addition, replenishment developers corresponding to developers (D-2) to (D-26) were obtained in the same manner as the preparation of the replenishment developer corresponding to developer (D-1). In Table 4, "diameter" indicates the number average primary particle diameter. "Parts" indicates parts by mass relative to 100 parts by mass of the coating resin. "StTiO3" indicates strontium titanate particles. "BaTiO3" indicates barium titanate particles. "CB" indicates carbon black. "CR" indicates crosslinked resin. "NCR" indicates non-crosslinked resin. "Si" indicates silica.

[0169] [Table 4]

[0170] [Evaluation machine] A trickle development type color multifunction printer (TASKalfa7054ci manufactured by Kyocera Document Solutions Inc.) was prepared as the evaluation machine. This color multifunction printer was mainly equipped with an amorphous silicon drum as a photoconductor and a two-component development device. The maximum printing speed of the above color multifunction printer was 70 sheets per minute. The development gap of the above color multifunction printer was 0.375 mm. When printing A4 size printing paper, the above color multifunction printer printed so that the width direction of the printing paper and the printing direction were aligned.

[0171] [Measurement of desorption rate] One of the developers (D-1) to (D-26) was loaded into the cyan developing device of the evaluation machine. Furthermore, a refill developer corresponding to each developer was loaded into the refill section of the cyan developing device of the evaluation machine. By performing intermittent printing using the evaluation machine, the detachment rate M of the spacer particles and the detachment rate N of the strontium titanate particles were measured. The measurement results are shown in Table 5 below.

[0172] Specifically, in an environment of 23.5°C temperature and 5% RH humidity, an evaluation machine was used to print 1000 sheets of A4 size printing paper with a pattern image (character pattern image) with a print rate of 1%. In the intermittent printing, a cycle of printing for 4.3 seconds and pausing printing for about 0.5 seconds was repeated. During the intermittent printing, the replenishment developer was continuously replenished at a constant speed so as not to change the toner concentration of each developer in the developing device.

[0173] For the evaluation machine after intermittent printing, a magnet was brought close to the developing roller to which the developer was attached, and the developer (developer after the printing durability test) was peeled off and collected from the developing roller. The developer after the printing durability test was separated into toner (toner after the printing durability test) and carrier (carrier after the printing durability test) by sucking air through a mesh.

[0174] (Spacer particle detachment rate M) For the developers (D-1), (D-4) to (D-22), and (D-25) to (D-26), the toners before and after the printing durability test were subjected to gas chromatography mass spectrometry, the details of which are shown below. As a result, the content of spacer particles (resin particles) in the toner particles for each toner was measured.

[0175] The content of spacer particles in the toner particles measured by analysis of the toner before the above-mentioned printing durability test was defined as M1. The content of spacer particles in the toner particles measured by analysis of the toner after the printing durability test was defined as M2. The detachment rate M of the spacer particles was calculated for each developer by applying M1 and M2 to the following formula (M). Desorption rate of spacer particles M = 100 × (M1-M2) / M1 (M)

[0176] For the developers (D-23) to (D-24), the toner before the printing durability test and the toner after the printing durability test were subjected to fluorescent X-ray analysis, the details of which are shown below. As a result, the content of spacer particles (spacer silica particles) in the toner particles was measured for each toner. The content of spacer particles in the toner particles measured by the analysis of the toner before the above-mentioned printing durability test was designated as M1. Moreover, the content of spacer particles in the toner particles measured by the analysis of the toner after the printing durability test was designated as M2. By applying M1 and M2 to the following formula (M), the apparent detachment rate m of the spacer particles was calculated for each developer. Apparent detachment rate of spacer particles m = 100 × (M1-M2) / M1 (M)

[0177] In the developers (D-23) to (D-24), base silica particles are contained as external additives together with spacer silica particles. Therefore, when the content of spacer silica particles contained in the toner particles of the developers (D-23) to (D-24) is quantified by fluorescent X-ray analysis, the total content of the spacer silica particles and base silica particles is detected. Here, since the number-average primary particle diameter of the base silica particles is small, it is determined that the particles do not essentially fall off. From the above, the apparent detachment rate m of the developers (D-23) to (D-24) is further corrected by the following formula (M'), and the calculated value is taken as the true detachment rate M. The corrected value was 0.675. True detachment rate of spacer particles M = correction value × apparent detachment rate m (M') Correction value = Amount of spacer silica particles used when preparing toner particles (3.11 parts by mass) / (Amount of base silica particles used when preparing toner particles (1.50 parts by mass) + Amount of spacer silica particles used when preparing toner particles (3.11 parts by mass))

[0178] (Desorption rate of strontium titanate particles M) The carriers before and after the printing durability test were subjected to fluorescent X-ray analysis under the following conditions, thereby measuring the content of strontium titanate particles in the carrier particles of each carrier.

[0179] The carrier before the printing test was analyzed to measure the content N1 of strontium titanate particles in the carrier particles. The carrier after the printing test was analyzed to measure the content N2 of strontium titanate particles in the carrier particles after the printing test. The detachment rate N of strontium titanate particles was calculated for each developer by applying N1 and N2 to the following formula (N). Desorption rate of strontium titanate particles N = 100 × (N1-N2) / N1 (N)

[0180] (X-ray fluorescence analysis) Using a tablet molding compression machine ("BRE-33" manufactured by Mayekawa Test Machinery Manufacturing Co., Ltd.), the measurement object (toner or carrier) was pressurized (pressure: 20 MPa, pressurization time: 3 seconds) to prepare a cylindrical pellet with a diameter of 10 mm. The obtained pellet was subjected to fluorescent X-ray analysis under the detailed conditions shown below to obtain a fluorescent X-ray spectrum (horizontal axis: energy, vertical axis: intensity (number of photons)). From the obtained fluorescent X-ray spectrum, the X-ray intensity (Si intensity or Sr intensity) of the peak derived from the measurement element (silicon when the measurement object is a toner, strontium when the measurement object is a carrier) was obtained. Based on the above-mentioned Si intensity or Sr intensity, the content of spacer silica particles in the toner particles or the content of strontium titanate particles in the carrier particles was calculated. In calculating the content of spacer silica particles, the measured Si intensity was applied to a calibration curve showing the relationship between the Si intensity and the content of spacer silica particles that had been prepared in advance. In calculating the content of strontium titanate particles, the measured Sr intensity was applied to a calibration curve that had been prepared in advance and shows the relationship between the Sr intensity and the content of strontium titanate particles.

[0181] (Details of X-ray fluorescence analysis conditions) Analytical equipment: Scanning X-ray fluorescence analyzer (Rigaku Corporation "ZSX PrimusIV") X-ray tube (X-ray source): Rh (rhodium) Excitation conditions: Tube voltage 50 kV, tube current 50 mA Measurement area (X-ray irradiation range): diameter 30 mm Measurement elements: Strontium or silicon

[0182] (Gas Chromatography Mass Spectrometry) In the gas chromatography mass spectrometry, a gas chromatograph mass spectrometer (Shimadzu Corporation, "GCMS-QP2010 Ultra") and a multi-shot pyrolyzer (Frontier Labs, Inc., "FRONTIER LAB Multi-functional Pyrolyzer (registered trademark) EGA / PY-3030D") were used as the apparatus. A GC column (Agilent Technologies, Inc., "Agilent (registered trademark) J&W Ultra Inert Capillary GC Column DB-5ms", phase: arylene phase in which arylene is added to siloxane polymer to strengthen the polymer main chain, inner diameter: 0.25 mm, film thickness: 0.25 μm, length: 30 m) was used as the column. The detailed conditions of the gas chromatography mass spectrometry were as follows.

[0183] (Details of gas chromatograph conditions) Carrier gas: Helium (He) gas Carrier flow rate: 1mL / min Vaporizer temperature: 210℃ Pyrolysis temperature: Heating furnace "600℃", interface part "320℃" Heating conditions: After holding at 40°C for 3 minutes, the temperature was raised from 40°C to 300°C at a rate of 10°C / min, and held at 300°C for 15 minutes.

[0184] (Details of mass analysis conditions) Ionization method: EI (Electron Impact) method Ion source temperature: 200℃ Interface temperature: 320℃ Detection mode: Scan (measurement range: 45m / z~500m / z)

[0185] By analyzing the mass spectrum and chromatogram measured under the above conditions, the peak area of ​​the peak derived from the crosslinking agent of the spacer particles (resin particles) in the measurement object (toner) was obtained. Then, based on the peak area, the content of the spacer particles in the toner particles was calculated. In calculating the content of the spacer particles, the measured peak area was applied to a calibration curve that shows the relationship between the peak area and the content of the spacer particles, which was prepared in advance.

[0186] <Evaluation> The developers (D-1) to (D-26) were evaluated for image density stability and the occurrence of fogging by the following methods. The evaluation results are shown in Table 5.

[0187] [Image density stability] Any one of the developers (D-1) to (D-26) was put into the cyan developing device of the evaluation machine. Furthermore, a refill developer corresponding to each developer was put into the refill section of the cyan developing device of the evaluation machine. Using the evaluation machine with each developer and refill developer put in, in an environment of 23.5°C temperature and 5% RH, a pattern image (character pattern image) with a print rate of 1% was intermittently printed on 1000 sheets of A4 size printing paper (first printing process). In the intermittent printing, a cycle of printing for 4.3 seconds and pausing printing for about 0.5 seconds was repeated. During the intermittent printing, the refill developer was continuously replenished at a constant speed so that the toner concentration in each developer in the development device would not change. After the first printing process, an evaluation image A including a solid image and a non-printed portion was printed on the printing paper.

[0188] Next, after the first printing process, a pattern image with a printing rate of 50% was continuously printed on 100 sheets of A4 size printing paper using the evaluation machine (second printing process). After the second printing process, an evaluation image B including a solid image and a non-printed area was printed on the printing paper.

[0189] Using a reflection densitometer (SpectroEye (registered trademark) manufactured by X-Rite), the image density (ID 1000) and the image density (ID 1100 The image density stability was evaluated according to the following criteria.

[0190] (Image density stability standard) A (particularly good): ID 1000 and ID 1100 Both are 1.20 or higher. B (good): ID 1000 and ID 1100 Both are 1.10 or higher. However, ID 1000 and ID 1100 At least one of these is less than 1.20. C (bad): ID 1000 and ID 1100 At least one of these is less than 1.10.

[0191] [Focus] Using a white light photometer (Tokyo Denshoku Co., Ltd. "TC-6DS"), the reflection density A of the non-printed area (blank area) of the evaluation image A, the reflection density B of the non-printed area (blank area) of the evaluation image B, and the reflection density C (background value) of the unprinted printing paper were measured. Reflection density A - reflection density C was calculated as the fog density (FD 1000 Reflection density B - reflection density C was defined as the fog density (FD 1100 The fog was judged according to the following criteria.

[0192] (Fog standard) A (particularly good): FD 1000 and FD 1100 are both less than 0.010. B (good): FD 1000 and FD 1100 Both are less than 0.020. However, FD 1000 and FD 1100 At least one of these is 0.010 or more. C (defective): FD 1000 and FD 1100 At least one of these is 0.020 or more.

[0193] [comprehensive evaluation] Each developer was comprehensively evaluated according to the following criteria. A (particularly good): Both image density stability and fog are rated as A. B (good): Both image density stability and fog are rated A or B. However, at least one of image density stability and fog is rated B. C (poor): At least one of image density stability and fog is rated C.

[0194] [Table 5]

[0195] As shown in Tables 1 to 5, the developers of Examples 1 to 20 included a carrier including carrier particles and a toner including toner particles. The carrier particles included carrier base particles and strontium titanate particles adhering to the surfaces of the carrier base particles. The carrier base particles included a carrier core and a coating layer covering the carrier core. The coating layer contained a coating resin, barium titanate particles, and carbon black. The coating resin contained a silicone resin. The toner particles included toner base particles and an external additive adhering to the surfaces of the toner base particles. The external additive contained base silica particles and spacer particles. The number-average primary particle diameter of the spacer particles was 35 nm or more and 200 nm or less. The coverage A of the spacer particles on the toner particles and the coverage B of the strontium titanate particles on the carrier particles satisfied the following formula (1). The detachment rate M of the spacer particles calculated by the following formula (M) and the detachment rate N of the strontium titanate particles calculated by the following formula (N) satisfied the following formula (2). A>B···(1) N>M···(2) M = 100 × (M1 - M2) / M1 (M) N = 100 × (N1 - N2) / N1 (N)

[0196] On the other hand, the carrier particles of the developer (D-1) of Comparative Example 1 did not contain strontium titanate particles. As a result, the developer (D-1) had poor image density stability.

[0197] The toner particles of the developer (D-2) of Comparative Example 2 did not have spacer particles. As a result, the developer (D-2) had poor image density stability and fogging.

[0198] In the developer (D-3) of Comparative Example 3, the carrier particles did not contain strontium titanate particles, and the toner particles did not contain spacer particles. As a result, the developer (D-3) had poor image density stability and fogging.

[0199] In the developer (D-4) of Comparative Example 4, the developer (D-20) of Comparative Example 5, and the developer (D-23) of Comparative Example 6, the detachment rate M of the spacer particles and the detachment rate N of the strontium titanate particles did not satisfy "N>M." As a result, the developers (D-4), (D-20), and (D-23) had poor fogging. [Industrial Applicability]

[0200] The two-component developer and image forming apparatus of the present invention can be used to form images in, for example, a copier, a printer, or a multifunction machine. [Explanation of symbols]

[0201] 1. Carrier particles 2. Carrier mother particles 2a Career Core 2b Coating layer 3 Strontium titanate particles 4 Toner particles 5 Toner base particles 6 External additives 6a Spacer particles 6b Base Silica Particles 40 Image forming device 41 Photoreceptor 42 Charging device 44 Developing device

Claims

1. A carrier including carrier particles and a toner including toner particles, the carrier particles include carrier base particles and strontium titanate particles attached to the surfaces of the carrier base particles, The carrier base particle has a carrier core and a coating layer that covers the carrier core, The coating layer contains a coating resin, barium titanate particles, and carbon black, The coating resin includes a silicone resin, The toner particles include toner base particles and an external additive attached to a surface of the toner base particles, The external additive includes silica particles and spacer particles, the number average primary particle diameter of the spacer particles is 35 nm or more and 200 nm or less; a coverage rate A of the spacer particles on the toner particles and a coverage rate B of the strontium titanate particles on the carrier particles satisfy the following formula (1), A two-component developer, wherein a detachment rate M of the spacer particles calculated by the following formula (M) and a detachment rate N of the strontium titanate particles calculated by the following formula (N) satisfy the following formula (2): A>B...(1) N>M... (2) M=100×(M 1 -M 2 ) / M 1 ・・・(M) N=100×(N 1 -N 2 ) / N 1 ・・・(N) (In the formulas (M) and (N), M 1 represents the content of the spacer particles in the toner particles, M 2 represents the content of the spacer particles in the toner particles after a printing durability test, N 1 represents the content of the strontium titanate particles in the carrier particles, N 2 represents the content of the strontium titanate particles in the carrier particles after the printing durability test, The printing durability test is a test in which a pattern image with a printing rate of 1% is intermittently printed on 1,000 sheets of A4 size printing paper, one by one, using the two-component developer, under an environment of a temperature of 23.5° C. and a humidity of 5% RH.

2. 2. The two-component developer according to claim 1, wherein the strontium titanate particles have a number average primary particle diameter of 15 nm or more and 100 nm or less.

3. 3. The two-component developer according to claim 1, wherein a content of the strontium titanate particles relative to 100.00 parts by mass of the carrier base particles is 0.01 parts by mass or more and 0.06 parts by mass or less.

4. 3. The two-component developer according to claim 1, wherein a number average primary particle diameter of the spacer particles is larger than a number average primary particle diameter of the strontium titanate particles.

5. 3. The two-component developer according to claim 1, wherein a coverage A of the spacer particles on the toner particles is 10.0 area % or more and 45.0 area % or less.

6. 3. The two-component developer according to claim 1, wherein a content of the barium titanate particles relative to 100 parts by mass of the coating resin is 3 parts by mass or more and 50 parts by mass or less.

7. 3. The two-component developer according to claim 1, wherein a coverage B of the strontium titanate particles on the carrier particles is 5.0 area % or more and 20.0 area % or less.

8. 3. The two-component developer according to claim 1, wherein the content of the carbon black is 3 parts by mass or more and 20 parts by mass or less with respect to 100 parts by mass of the coating resin.

9. 3. The two-component developer according to claim 1, wherein a detachment rate M of the spacer particles is 3% or more and 40% or less.

10. 3. The two-component developer according to claim 1, wherein the detachment rate N of the strontium titanate particles is 50% or more and 70% or less.

11. The two-component developer according to claim 1 or 2, A photoconductor; a charging device for charging the surface of the photoreceptor; a developing device that supplies the toner to a surface of the photoconductor and develops the toner image, The printing durability test is carried out using the image forming apparatus.

Citation Information

Patent Citations

  • Carrier for electrophotographic developer, developer and process cartridge

    JP2005091878A